Clinical and molecular characterization of Wilson's disease in China: identification of 14 novel mutations - De-Min Yu; Zhou Feng; Zang Guo-Qing; Xu Jie; Fu Qing-Chun; Ling Yun; Lu Yi; Li Xin-Hua; Han Yue; Zhang Dong-Hua; Gong Qi-Ming; Lu Zhi-Meng; et al. (BMC, 2011)
Abstract Background Wilson's disease (WND) is a rare autosomal recessive disorder. Here we have evaluated 62 WND cases (58 probands) from the Chinese Han population to expand our knowledge of ATP7B mutations and to more completely characterize WND in China. Methods The coding and promoter regions of the ATP7B gene were analyzed by direct sequencing in 62 Chinese patients (58 probands) with WND (male, n = 37; female, n = 25; age range, 2 ~ 61 years old). Results Neurologic manifestations were associated with older age at diagnosis (p < 0.0001) and longer diagnostic delay (p < 0.0001). Age at diagnosis was also correlated with urinary copper concentration (r = 0.58, p < 0.001). Forty different mutations, including 14 novel mutations, were identified in these patients. Common mutations included p.Arg778Leu (31.9%) and p.Pro992Leu (11.2%). Homozygous p.Arg778Leu and nonsense mutation/frameshift mutations were more often associated with primary hepatic manifestations (p = 0.0286 and p = 0.0383, respectively) and higher alanine transaminase levels at diagnosis (p = 0.0361 and p = 0.0047, respectively). Nonsense mutation/frameshift mutations were also associated with lower serum ceruloplasmin (p = 0.0065). Conclusions We identified 14 novel mutations and found that the spectrum of mutations of ATP7B in China is quite distinct from that of Western countries. The mutation type plays a role in predicting clinical manifestations. Genetic testing is a valuable tool to detect WND in young children, especially in patients younger than 8 years old. Four exons (8, 12, 13, and 16) and two mutations (p.Arg778Leu, p.Pro992Leu) should be considered high priority for cost-effective testing in China.